2024
DOI: 10.1093/eurjpc/zwad409
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of foods and beverages rich in added sugar associated with incident metabolic syndrome: the Coronary Artery Risk Development in Young Adults (CARDIA) study

Rae K Goins,
Lyn M Steffen,
So-Yun Yi
et al.

Abstract: Aims Numerous studies report positive associations between total carbohydrate (CHO) intake and incident metabolic syndrome (MetS), but few differentiate quality or type of CHO relative to MetS. We examined source of CHO intake, including added sugar (AS), AS-rich CHO foods and sugar-sweetened beverages (SSBs) associated with incident MetS in adults enrolled in the Coronary Artery Risk Development in Young Adults (CARDIA) study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, only one clinical dietary intervention study has been conducted comparing the effects of sustained consumption of liquid versus solid sugar, and a significant group difference in body weight was not observed ( 138 ). Importantly, a recent prospective study found that both added sugar in food and added sugar in beverage increased the risk of developing metabolic syndrome during a 30-year follow-up ( 140 ). Therefore, more studies comparing liquid versus solid sugar are needed to determine whether the consumption of liquid sugar is more detrimental than solid sugar and investigators need to be aware of this.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, only one clinical dietary intervention study has been conducted comparing the effects of sustained consumption of liquid versus solid sugar, and a significant group difference in body weight was not observed ( 138 ). Importantly, a recent prospective study found that both added sugar in food and added sugar in beverage increased the risk of developing metabolic syndrome during a 30-year follow-up ( 140 ). Therefore, more studies comparing liquid versus solid sugar are needed to determine whether the consumption of liquid sugar is more detrimental than solid sugar and investigators need to be aware of this.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%